Avaliação de alterações comportamentais e oxidativas no cérebro e intestino de ratos submetidos a separação materna: influência do sexo e do tratamento com escitalopram e doxiciclina - Gomes, Nayana Soares (2019)
Early life adversity (ELA) events can trigger several mental disorders, such as anxiety and depressive disorder. Maternal separation (MS), one form of ELA, is related to the development of depression and development of inflammatory bowel disease in adulthood. The pathophysiology of depression involves changes in monoamines, neuroinflammation, neuro-oxidative/nitrosative stress, and reduction of neurotrophic factors, such as brain-derived neurotrophic factor (BDNF). Despite the advances in the understanding of depression, the influence of sex on the neurobiology of this disorder is not elucidated. The present study aimed to verify the influence of sex in the depressive-like and working memory alterations of animals exposed to MS and to verify alterations in neuro-oxidative/nitrosative stress, neuroinflammation, neurotrophic and intestinal microbiota, besides evaluating the reversal of these changes by the antidepressant strategies escitalopram (ESC) or doxycycline (Doxy). Wistar rats of both sexes were submitted to MS or left with their mothers (controls) between postnatal days (PNs) 1 to 15, and during adulthood between PN60 and 73. Part of these animals was treated with saline (controls) and other part with ESC or Doxy. On PN74, the animals were submitted to behavioral tests of forced swimming (for the evaluation of depression), Y maze (working memory) and locomotor activity. After the tests the feces were collected and the cerebral areas, namely prefrontal cortex (PFC), hippocampus and striatum (ST) were dissected, as well as segments of the intestine. The levels of GSH, myeloperoxidase activity, lipid peroxidation (PL) and nitrite were evaluated in the PFC, hippocampus, ST and intestine, while BDNF and interleukin 6 (IL-6) were evaluated in the hippocampus. To date, the determination of total bacteria by qPCR technique in the gut was performed as an initial experiment to determine changes in phyla relevant to depression. The results showed that male and female MS animals presented increased immobility time in forced swimming when compared to controls, an indicative of depressive-like behavior. Both ESC and doxy were effective in the treatment of females, but not males. We did not observe changes in working memory, while the locomotor activity of male animals treated with doxy was reduced relative to controls. Males MS treated with doxy increased the number of groomings in relation to controls, showing a possible anxious behavior, while the MS females presented anxiety reduction evidenced by the increase of permanence in the center of the open field. In the neurochemical parameters we observed that the animals showed: increase of BDNF (females) in both MS animals treated with ESC and doxy; increased IL-6 (females) in MS animals; reduction of GSH that was reversed by the ESC and doxy (males and females); increased lipid peroxidation and nitrite (females) that was reversed by ESC and doxy. In the gut, we observed that both males and females presented increased MPO activity and reduction of GSH in the jejunum. In conclusion, our results show that females are more susceptible to the effects of MS on symptoms of depression and neurochemical changes triggered by this disorder, while both males and females are susceptible to gut changes triggered by MS.